Modern Trends In Development Of Scientific And Technical Terminology In Architecture And Construction - Dekhkanov Bakhodir Ibrokhimovich (Peerian Journals Publishing, 2025)
The paper is an analysis of current changes and developments in the field of terminology in construction science and technology. The study focuses on the influence of contemporary technological changes and innovations on the formation of new terms, their usage in scientific and engineering areas of construction, as well as the interrelation between technological development and terminology evolution.
Keywords: Scientific and Technical Terminology; Construction